Ferulic acid amide derivatives with varying inhibition of amyloid-β oligomerization and fibrillization. (1st August 2021) - Kolaj, Igri; Wang, Yanfei; Ye, Kailin; Meek, Autumn; Liyanage, S. Imindu; Santos, Clarissa; Weaver, Donald F.
Graphical abstract: Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized, in part, by the misfolding, oligomerization and fibrillization of amyloid-β (Aβ). Evidence suggests that the mechanisms underpinning Aβ oligomerization and subsequent fibrillization are distinct, and may therefore require equally distinct therapeutic approaches. Prior studies have suggested that amide derivatives of ferulic acid, a natural polyphenol, may combat multiple AD pathologies, though its impact on Aβ aggregation is controversial. We designed and synthesized a systematic library of amide derivatives of ferulic acid and evaluated their anti-oligomeric and anti-fibrillary capacities independently. Azetidine tethered, triphenyl derivatives were the most potent anti-oligomeric agents (compound 2i : IC50 = 1.8 µM ± 0.73 µM); notably these were only modest anti-fibrillary agents (20.57% inhibition of fibrillization), and exemplify the poor correlation between anti-oligomeric/fibrillary activities. These data were subsequently codified in an in silico QSAR model, which yielded a strong predictive model of anti-Aβ oligomeric activity (κ = 0.919 for test set; κ = 0.737 for validation set).